Effect of addition cobalt nanoparticles on Sn-Ag-Cu lead-free solder - Tay, S.L.; Haseeb, A.S. Md. Abdul; Johan, Mohd Rafie (2010)
Nowadays, nanoelectroctronic, electro-nanotechnologies environmental friendly products become the roadmap in industry. Hence, nanoscale of reinforcement into lead-free solder becomes more popular rather than the micro size of reinforcement. In this paper, Cobalt nanoparticles-reinforced Sn-Ag-Cu composite solders were prepared by thoroughly blending 0.75 wt% of cobalt nanoparticles with near eutectic cement tended to suppress the growth of Cu3Sn intermetallic layer. However, upon addition of Co nanoparticles, the growth of Cu6Sn5 was enhanced. The distribution of the Co nanoparticles was observed by the elemental mapping which was carried out by using electron micro probe analysis (EPMA) and transmission electron microscopy which equipped together with electron-dispersive X-ray spectroscopy (TEM-EDX). There was no Co detected in the Cu3Sn, it only presented in Cu6Sn5. The interdiffusion coefficient was increased with the ageing temperature. Upon additionof Co nanoparticles, the interdiffusion coefficient for the formation of Cu3Sn intermetallic layer was reduced, but the interdiffusion coefficient for the formation of Cu6Sn5 layer was increased. The activation energy for the formation of Cu3Sn was also increased with the Co addition.